The Impact of Pandemics on External Audit Practices - Noora AlSuwaidi; Alya Houti; Walaa Wahid ElKelish; Magdi El-Bannany (Asian Journal of Business and Accounting, 2024)
Manuscript type: Research paper Research aims: This paper investigates the extent and determinants of pandemics such as COVID-19 on external auditing practices in the United Arab Emirates (UAE) emerging market. Design/Methodology/Approach: An explanatory study was conducted using the deductive research approach. This paper uses the multiple regression analysis model (OLS) to analyse the survey questionnaire posted to several accountants and auditors. This paper utilizes the foundations of the Contingency Theory to support the study hypotheses. Research findings: The findings shows that there is neutral relationship between the COVID-19 pandemic and the external auditing practices in the UAE emerging market. More specifically, respondents show moderate perceptions on the negative impact of COVID-19 on auditing performance, functions and skills. The most important determinants of auditing practices risk include firm size, respondents’ job rank, education and gender. Theoretical contribution/Originality: This paper adds to existing literature the impact of the COVID-19 pandemic on external auditing performance, functions and skills in an emerging market such as the UAE. In addition, it highlights most important determinants of the relationship between the COVID-19 pandemic and the auditing practices. Practitioner/Policy implication: This paper improves auditing performance by focusing on appropriate policies to improve audit evidence for the required standards during pandemics. Research limitations/Implications: The study is limited to a single emerging market. Future studies can increase the sample size and conduct triangulation research methodology to enrich the research findings.